2022
DOI: 10.1165/rcmb.2021-0364oc
|View full text |Cite
|
Sign up to set email alerts
|

The Type 2 Asthma Mediator IL-13 Inhibits Severe Acute Respiratory Syndrome Coronavirus 2 Infection of Bronchial Epithelium

Abstract: Asthma is associated with chronic changes in the airway epithelium, a key target of SARS-CoV-2. Many epithelial changes, including goblet cell metaplasia, are driven by the type 2 cytokine IL-13, but the effects of IL-13 on SARS-CoV-2 infection are unknown. We found that IL-13 stimulation of differentiated human bronchial epithelial cells (HBECs) cultured at air-liquid interface reduced viral RNA recovered from SARS-CoV-2 infected cells and decreased dsRNA, a marker of viral replication, to below the limit of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 56 publications
(83 reference statements)
2
37
0
Order By: Relevance
“…A recent study showed that, despite mucus removal, IL-13 treatment had protective effects against SARS-CoV-2 infections ( 37 ). Our infections were performed via bolus (200 µL) incubation for 2 h, and this approach was shown to remove the majority of the mucus from the cell surfaces ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that, despite mucus removal, IL-13 treatment had protective effects against SARS-CoV-2 infections ( 37 ). Our infections were performed via bolus (200 µL) incubation for 2 h, and this approach was shown to remove the majority of the mucus from the cell surfaces ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Relative abundance of MUC5AC was analyzed by mucin Western blotting ( 55 ). Gene expression data were obtained from NCBI GEO and processed using R. CBF was determined by taking phase contrast videos of the field of view and performing Fourier spectral analysis ( 37 ). MCT velocity was obtained by tracking hardened red blood cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible mechanism is the reduction of angiotensinconverting enzyme-2, the host cell entry receptor for SARS-CoV-2 in people with asthma. 25 Although there were differences in percent tested among the occupational groups, the correlation between the percent tested work and in situations outside of work. 27,28 Information on trends in infection risk for detailed occupations and for major occupational groups can help target messaging and future studies on specific working or social conditions contributing to risk of infection and lead to improved mitigation strategies.…”
Section: Detailed Occupational Categoriesmentioning
confidence: 97%
“…It is suggested that allergic inflammation and the type 2 (T2)-high asthma might convey some forms of protection from SARS-CoV-2 infection, whereas T2-low asthma might be a risk factor of COVID-19 13 . It is based on the contrasting epidemiological observations in COVID-19 cohorts from different parts of the world 11, 13 , and a few mechanistic studies showing that IL-13, the major type 2 cytokine, decreases ACE2 expression and inhibits SARS-CoV-2 infection in airway epithelium 14, 15 . However, IL-13 has been also shown to be a major driver of COVID-19 severity and anti-IL-4/13 treatment is showing positive effects in COVID-19 clinical trials 16, 17 .…”
Section: Introductionmentioning
confidence: 99%